Development of e-books for grade VIII social studies in the independent curriculum - Angelina Stephani Manullang; Aisiah Aisiah (SCHOULID: Indonesian Journal of School Counseling, 2025)
This research is motivated by the students' need for Social Studies (IPS) learning resources in the form of an e-book that is contextual, engaging, technology-based (utilizing Canva, Augmented Reality, and Heyzine), and integrates the local history of West Sumatra. The purpose of the research is to identify the stages of development, assess the feasibility, practicality, and effectiveness of the Social Studies Grade VIII e-book for the Independent Curriculum. This study employed a research and development method using the ADDIE model. The research subjects involved experts (lecturers), teachers, and students. The feasibility testing involved three experts: one in historical content, one in language, and one in media and learning resources. The subjects for testing practicality and effectiveness consisted of one Social Studies teacher and 31 Grade VIII-1 students of SMP Maria Padang, including 12 boys and 19 girls. Data collection instruments included feasibility, practicality, and effectiveness questionnaires. Data analysis was conducted using qualitative and quantitative approaches. The development of the Grade VIII Social Studies e-book followed five stages: (1) Analysis – identifying development needs through curriculum review and textbook evaluation, revealing the lack of local West Sumatran history content; (2) Design – structuring the e-book by combining national and Minangkabau history using Canva and Heyzine, and integrating HOTS and AKM-based questions via Wordwall, Quizizz, and Google Forms; (3) Development – validating the e-book with assessments from history, media, and language experts; (4) Implementation – integrating the e-book into learning activities and collecting practicality and effectiveness data from students; (5) Evaluation – gathering feedback through questionnaires to identify strengths and weaknesses. The e-book was rated as interesting, easy to use, and its interactive features (AR and Quizizz) were effective in enhancing students’ understanding of local history. Feasibility test results showed high ratings from the history expert (average score 3.44), media and learning expert (3.31), and language expert (3.78). Practicality and effectiveness tests also yielded very high scores: 3.73 from the teacher and 3.67 from students. The study concludes that the Grade VIII Social Studies e-book for the Independent Curriculum is highly feasible, practical, and effective as a supplementary learning resource that integrates local West Sumatran history and digital technology.